Artificial Intelligence and the Future of Higher Education: Towards Inclusive, Ethical, and Employability-Driven Learning Ecosystems (Critique Open Research & Review, 2025)
Artificial Intelligence (AI) is revolutionising higher education by generating novel opportunities for inclusive learning, skill enhancement, and equal access to information. This chapter analyses the influence of AI on higher education, emphasising its contribution to fostering diversity, improving employability skills, and mitigating gender inequities. AI-driven solutions, including adaptive learning platforms, automated feedback systems, and natural language processing technologies, provide the capability to customise the learning experience, assist students with varied needs, and enhance academic English proficiency. Moreover, AI-powered career development solutions are transforming employability training through real-time feedback, workplace simulations, and focused skill enhancement interventions. Nonetheless, whereas AI presents opportunity to bridge educational disparities, it simultaneously engenders worries about algorithmic bias, ethical dilemmas, and data privacy vulnerabilities. While reviewing literature, this chapter examines AI's capacity to enhance inclusive education while critically evaluating the dangers of unequal access and algorithmic bias. It promotes a balanced approach that emphasises human-centred education, gender equality, and preparedness for employment. The findings enhance the overarching dialogue regarding AI in education, impacting policy deliberations and institutional approaches to fostering equal learning environments in the digital era.